2005
DOI: 10.1109/tnn.2005.853417
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Neural-Based Buffer Management for Queuing Systems With Self-Similar Characteristics

Abstract: Index Terms-Buffer management, fairness, neural network teletraffic forecasting, packet loss, water-filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Many models have been developed to characterize selfsimilar traffic or generate self-similar traffic traces (e.g., [12], [17]). Among the developed models, Fractional Brownian Motion (FBM) is an efficient and widely used way for modelling and generating self-similar traffic and is thus adopted in this paper.…”
Section: Queueing Systems With Self-similar Trafficmentioning
confidence: 99%
“…Many models have been developed to characterize selfsimilar traffic or generate self-similar traffic traces (e.g., [12], [17]). Among the developed models, Fractional Brownian Motion (FBM) is an efficient and widely used way for modelling and generating self-similar traffic and is thus adopted in this paper.…”
Section: Queueing Systems With Self-similar Trafficmentioning
confidence: 99%
“…The seminal work of Leland et al [8] has triggered an explosion of research on traffic self-similarity (e.g., [14,26,29]), which has been discovered as a ubiquitous phenomenon in modern communication networks and multimedia systems, including wired local-area networks [8], wide-area networks [21], wireless and mobile networks [9,22], World Wide Web [5], and Variable-Bit-Rate (VBR) video systems [2]. So far, many models have been developed to characterize traffic self-similarity or generate self-similar traffic traces.…”
Section: Modeling Self-similar Trafficmentioning
confidence: 99%
“…Their work has triggered an explosion of research on this subject (e.g., [28][29][30]). Many subsequent studies have further demonstrated traffic self-similarity be a ubiquitous phenomenon in a variety of telecommunication systems [9][10][11][12][13].…”
Section: Self-similar Trafficmentioning
confidence: 99%